PENGARUH PROGRAM FCS DAN KERJA SAMA LUAR NEGERI TERHADAP MINAT MAHASISWA BARU DI STIPRAM YOGYAKARTA - Moch. Nur Syamsu; Agung Yuliyanto Nugroho (Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to analyze the influence of the Foreign Case Study (FCS) Program and international collaboration on the interest of new students in choosing the Tourism Study Program at the Ambarrukmo Tourism College (STIPRAM). The internationalization of tourism higher education is an important strategy in increasing institutional competitiveness amidst global competition, so an empirical study is needed to measure the effectiveness of the implemented international programs. This study uses a quantitative approach with a survey method on new students of the Tourism Study Program at STIPRAM. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS software. The results show that the FCS Program has a positive and significant effect on the interest of new students, with a path coefficient value of 0.41 and a p-value <0.05. In addition, international collaboration also has a positive and significant effect, with a line coefficient of 0.47 and a p-value <0.05. Simultaneously, the two exogenous variables are able to explain 63% of the variation in new students' interest, indicating that the research model has strong explanatory power. These findings demonstrate that international experiential learning programs and global institutional networks play a role in shaping prospective students' perceptions and interests in tourism education. This research provides an empirical contribution to the development of tourism management research, particularly regarding the internationalization strategies of higher education institutions. Practically, the results can serve as a basis for tourism institution managers in designing and optimizing international programs to increase the interest and quality of new students.